Determinación de la composición física, química y bateriológica de efluentes de residuos sólidos orgánicos del camal municipal de Moyobamba, con la finalidad de uso sostenible local - Chavez Tavara, Jhefferd Merlimg (2017)
The project was carried out in the province and Moyobamba District, in the year 2015, needing to do some tests during the first months of 2016. The specific objectives are: to collect Municipal Camal effluents for physical, chemical and bacteriological analysis and their action on irrigated soil for local sustainable use; and indicate the effluent management process generated in the Municipal Camal, for local sustainable use. The parameters evaluated are turbidity. PH, Conductivity, Fecal Coliforms, SST, BOD5, COD, Total Phosphorus and Ammonia Cal Nitrogen. The determination was made in the laboratory, then compared with the Maximum Permissible Limits (LMP). In addition, the physical and chemical analysis of two soil samples currently irrigated by gravity with the effluent from the municipal road of Moyobamba was carried out. The results of the analysis of three samples of effluents taken outside the perimeter of the Moyobamba Municipal Camal, at different times of the year, reported that they contain, on average, Turbidity 301.44 UNT; Ammonia Cal nitrogen 36.39 mg / L; Total Phosphorus 17.33 mg / L; COD 717.11 mg / L; BOD5 391.56 mg / L; Total Soluble Solids 371.22 mg / L; Fecal Coliforms 3534.78 CFU / 100mL; Electrical Conductivity 119.11 uS / cm; PH 4.72. The values obtained for each parameter in the three analyzes are greater than the PML in Turbidity, COD, BOD5, SST, and Fecal Coliforms; while the values of ammonia Cal nitrogen, total phosphorus and pH are below the PML. Soil analysis values obtained showed that the effluent from the municipal road of Moyobamba as it passes through the superficial surface layer, at the two sampling points (at 50m and 100m of irrigated distance), if they leave chemical elements required by the plants, which (N) with 0.431% and 0.220%, Phosphorus (P) with 19.68 ppm and 23.65 ppm, Potassium (K) with 265.80 ppm and 166.40 ppm; While it was normal for Calcium (Ca) with 16.40 meq / 100g of soil in both samples; In addition they presented high values of the CIC with 43.06 and 20.31; The electrical conductivity of both samples were 0.00067 and 0.00140 dS / m indicating very slightly saline, the pH of both samples were 6.42 and 6.13. When collecting Municipal Camal effluents for the physical, chemical and bacteriological analysis and their composition in the irrigated soil for local sustainable use purposes, we find that there are high contents of necessary elements for the plants, among them ammonia Cal nitrogen with 36.39 mg / L , Total phosphorus with 17.33 mg / L, and its composition in the irrigated soil with high values of N with 0.431% and 0.22%, P with 19.68 and 23.65 ppm, K with 265.80 and 166.40 ppm., Calcium with 36 and 16.4 meq / 100 g of soil, Magnesium with 5.40 and 2.46 meq / 100g of soil; The process of management of the effluent generated in the Camal Municipal, according to the tests carried out for the local sustainable use it is proposed to collect in tanks, to make aggregates with solutions of ash from the husk of rice coming from the brick blocks (20%), more aggregates Of grouts of magnecal (to 10%), in order to obtain foliar fertilizer.